Multi-MOSFET–controlled half bridge AC–AC converter for induction heating application. Issue 8 (11th June 2021) - Ramesh Babu, A.; SundarRajan, G. T.; Barnabas Paul Glady, J.; Geetha, V.
ABSTRACT: This article proposes a multi-MOSFET–controlled AC–AC half bridge converter for induction heating application. Here, the utility frequency is converted to high-frequency supply with the PWM technique without any DC stage. The forward voltage drop and the power loss are reduced to the maximum by inclusion of AC–AC resonant converter in the circuit for the induction heating application. The proposed converter is simulated with PID controller, fuzzy controller and hybrid controller. The simulation focuses on the performance index parameters such as efficiency, power factor, settling time and THD.